(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to explain the importance of social heritage and the resulting social relationships, which lead to an increase in social relationships that have suffered atrophy over the past several decades due to the impact of financial conditions. Studying social heritage is one of the reasons that may preserve these customs and traditions, and it is noticeable During the preparation of this study, some of them were not limited to the city of Zuwarah, the subject of research, but rather: We have found that there are customs and traditions that exist in neighboring cities, including in the case of death and marriage, with a slight difference in some social aspects. Due to the importance of this topic, we tried to devote our effort to the social conditions that need to be revived, and this is what we have shown during this study. Full knowledge of what is happening in the Zuwarah community socially.